2000
DOI: 10.1002/chin.200007081
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: General Syntheses of Optically Active α‐Trifluoromethylated Amines via Ring‐Opening Reactions of N‐Benzyl‐2‐trifluoromethylaziridine.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The aminoalcohol intermediates 11a-f having bis(4-fluorophenyl) or bis(6-fluoro-3-pyridyl) groups were prepared from esters 5, 15a 6, 7, 15b 8, 15c and 9 15d (Scheme 1). Esters 5-8 were converted to 10a-d by coupling with 4-fluorophenylmagnesium bromide, followed by provided the corresponding aziridines 12a-f. 16 The aziridine ring was opened using sodium azide to give 13a-f, 17 which were reduced by hydrogenation to give diamines 14a-f. 18 Formation of the imidazoline rings of 1c-f, 1g′, and 1h-i was accomplished using reaction conditions d 19 or e, 20 and 21a). The stereochemistry of the 1-position of 18 and 21a was supported by nuclear Overhauser effect (NOE) studies of the corresponding morpholinone and piperazinone derivatives 23 and 24, as shown in Figure 2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aminoalcohol intermediates 11a-f having bis(4-fluorophenyl) or bis(6-fluoro-3-pyridyl) groups were prepared from esters 5, 15a 6, 7, 15b 8, 15c and 9 15d (Scheme 1). Esters 5-8 were converted to 10a-d by coupling with 4-fluorophenylmagnesium bromide, followed by provided the corresponding aziridines 12a-f. 16 The aziridine ring was opened using sodium azide to give 13a-f, 17 which were reduced by hydrogenation to give diamines 14a-f. 18 Formation of the imidazoline rings of 1c-f, 1g′, and 1h-i was accomplished using reaction conditions d 19 or e, 20 and 21a). The stereochemistry of the 1-position of 18 and 21a was supported by nuclear Overhauser effect (NOE) studies of the corresponding morpholinone and piperazinone derivatives 23 and 24, as shown in Figure 2.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of the imidazoline derivatives 1c − i from aminoalcohols 11a − f is shown in Scheme . Treatment of the aminoalcohols 11a − f with triphenylphosphine and bromine provided the corresponding aziridines 12a − f . The aziridine ring was opened using sodium azide to give 13a − f , which were reduced by hydrogenation to give diamines 14a − f .…”
Section: Introductionmentioning
confidence: 99%
“…3 For example, in 2009, Shibata reported the enantioselective trifluoromethylation of imine with Me 3 SiCF 3 by employing Cinchona alkaloids as chiral catalysts. 3h The other process is the asymmetric transformation of the fluorinated block, 4 such as nucleophilic additions to fluorinated imines, 5 isomerization of fluorinated imines, 6 ring opening reaction of active trifluomethylated epoxides, 7 and kinetic resolution of racemic trifluoromethyl amines. 8 It is noteworthy that asymmetric hydrogenation of fluorinated imines/enamides is regarded as one of the most straightforward and atom-economic methods toward the synthesis of chiral trifluoromethylated amines.…”
mentioning
confidence: 99%